The Campus Canopy,1940-10-04 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, October 4, 1940. Vol. 7, No. 3. -- Hugh Hodgson To Present Recital Tuesday Evening -- Hendrick Wins Race For Junior Presidency -- 20 Girls To Wear Sock And Buskin Black Stockings -- Summer Names 10 Reporters To Canopy Staff -- Sophs Elect Thompson And O’Neal To Offices -- Student Councils Adopt New Plan -- 13 Selected For Vesper Choir -- Sociology Club Extends Bids To 28 Students -- Fire Causes Pandemonium On Campus -- Elizabeth Koblenzer, First Foreign Student At G. S. W. C., Creates Sensation
Digitized from original print, Valdosta State University Archives and Special Collections, January 17, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; Valdosta State College; Valdosta State University; GSWC; VSC; VSU; 1940; 1940s